Spectroscopic investigation on molecular aspects and structural and functional effects of tetraethyl pyrophosphate organophosphorus insecticide interaction with adult human hemoglobin. Issue 17 (22nd November 2022) - Doroudian, Aida; Hosseinzadeh, Reza; Maghami, Parvaneh; Khorsandi, Khatereh
Abstract: Organophosphates are extremely toxic compounds that use extensively in agriculture and household as insecticides. However, their binding mechanism to bio-macromolecules especially blood proteins is not clearly understood. In this research, various spectroscopic techniques utilized to analyze the effect of Tetraethyl Pyrophosphate (TEPP), as an organophosphorus insecticide, on the structure, function, stability, and aggregation of adult human hemoglobin and also hemolysis potential of the TEPP on red blood cells (RBCs) examined. Molecular docking was used for TEPP binding to human Hemoglobin (Hb), too. The results demonstrated that the TEPP insecticide has the potential for lysing RBCs. UV-Vis experiment indicated that globin part and heme group influenced by TEPP. Oxygen affinity measurements revealed the formation of deoxy-Hb and met-Hb, also decreased in oxygen affinity of Hb upon interaction with TEPP that is due to heme destruction. Fluorescence spectroscopy confirmed the production of heme degradation species after interaction of Hb with TEPP, which is inconsistent with oxygen affinity measurements. Thermal and aggregation studies indicated that TEPP induced aggregation of Hb in a concentration manner and Tm of protein reduced to lower temperatures. Docking's study also showed that TEPP interacts with Hb through hydrophobic interactions, which confirms UV-Vis results. ATR-FTIR study also revealed that TEPP can induce changes in the alpha helix element of Hb's secondary structure. Totally, Experimental and theoretical results indicate that tetraethyl pyrophosphate has unfavorable effects on hemoglobin structure and function. Communicated by Ramaswamy H. Sarma